Pengaruh Keterampilan Kerja, Kompensasi, dan Motivasi Terhadap Kinerja Karyawan (Studi Kasus Pada karyawan Bagian Produksi PT. Sumber Wijaya Sakti) - Chaliza, Aniek Noer (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study began with findings showing that employee performance at PT. Sumber Wijaya Sakti where employees are less than optimal in carrying out their work, so that the company's productivity in its targets is not achieved optimally. It can be seen in the monthly production results which show that employees who worked during a certain period were only able to produce a number of cigarettes that were much lower than the target that had been set as well as the finding that the variables that explain the phenomenon of employee performance are still different which then leads to the formulation of the problem regarding "how improve employee performance”. Departing from the problem formulation, this research aims to determine the influence of work skills, compensation and motivation on the performance of PT employees. Source Wijaya Sakti. This study uses a quantitative approach. The population in this study were employees of the production department of PT. Sumber Wijaya Sakti, totaling 163 employees with a sample of 116 employees. The sampling technique used is probability sampling with a simple random sampling method. In collecting data, this research used a Likert scale with 5 assessment criteria to measure 20 question items. The data analysis technique used is multiple linear regression analysis. The research results show that the work skills variable has a positive and significant effect on employee performance with a contribution of 26.6%. Compensation has a positive and significant effect on employee performance with a contribution of 27.2%. Motivation has a positive and significant effect on employee performance with a contribution of 44.3%. Meanwhile, work skills, compensation and motivation simultaneously influence the performance of PT employees. Sumber Wijaya Sakti is 51.9% and the remaining 48.1% is influenced by other variables not discussed in this research